The Development of East Natuna Block for Defense’s Interest on the Borderline and Securing Indonesia Energy Reserves - Amelia Gustin, Debby Rizqie (Department of International Relations Universitas Pertamina, 2022)
Natuna sea is Indonesia’s energy storage. East Natuna field, located on Indonesia's continental shelf in the Natuna sea, is believed to be the largest gas field in Asia-Pacific. Deposits a tremendous amount of hydrocarbon reserve potential numbered 46 TCF. The reserve is highly potential to meet Indonesia's future energy demand and is also an asset for national development. On the other hand, there could be a possibility that others also seek these natural resources. Part of the Natuna sea, which holds an extraordinary amount of hydrocarbon, is included in China's nine-dashed line claim of the South China Sea, an area with prolonged conflict. Indonesia's interest in maintaining our sovereignty over resources management on our continental shelf in the Natuna sea, particularly in managing energy resources. To achieve this interest, support for excellent defense capabilities is necessary. This research puts the synergy of energy and defense under scrutiny, exercising the quantitative method while seeking the help of qualitative methodology. Developing oil and gas fields on the borderline requires defense capability support to minimize threats. On the other hand, expenditure for strengthening, operating, and maintaining defense capability is costly. Benefit-cost analysis showed that defense expenditure for Natuna Island is far below the government's potential income from the development of the East Natuna field. This research concludes that Natuna island holds strategic values for politics, economy, and national defense. Energy resources in the Natuna Sea are assets for national development. Therefore it must be guarded. Thus, economic feasibility should not be the only basis for developing oil and gas in the Natuna sea. Even though another point of view, such as the development of those fields, is a state practice of Indonesia to maintain our sovereignty over the Natuna Sea and as an attempt to strengthen national defense on the borderline.